Pharyngeal Airspace Alterations after Using the Mandibular Advancement Device in the Treatment of Obstructive Sleep Apnea Syndrome - Pedro Dias Ferraz; Inês Francisco; Maria Inês Borges; Adriana Guimarães; Fátima Carvalho; Francisco Caramelo; José Pedro Figueiredo; Francisco Vale (Life, 2022)
Background: Mandibular Advancement Devices (MADs), inserted in non-surgical treatments for obstructive sleep apnea and hypopnea syndrome (OSAHS), are used intra-orally during the sleep period, with the aim of promoting mandibular protrusion. The aim of the study is to analyze the changes in the upper airway after the use of an MAD in the treatment of OSAHS. Methods: 60 patients diagnosed with OSAHS, as established by the Sleep Medicine Service, underwent treatment with the Silensor SL device at the Stomatology Service of the University Hospital Center of Coimbra, from January 2018 to January 2019. All patients completed two polysomnographies and two lateral teleradiographies: one before starting treatment (T0) and one after 1 year of treatment (T1). In the lateral teleradiography performed after one year of treatment, the patient had the MAD placed intra-orally. The linear measurements of the airspace proposed by the Arnett/Gunson FAB Surgery cephalometric analysis were measured at four craniometric points: A, MCI, B, Pog. Results: The results demonstrate an anteroposterior airway enlargement in two of the four points studied with the MAD placed intra-orally (B and Pog point). The greatest average increase is observed at point Pog (3 mm), followed by B (1 mm), and finally, point A (0.6 mm). Conclusions: This study proved that there is an improvement in anteroposterior measurements at various points in the upper airways after treatment with MAD.